Trophic guild and forest type explain phyllostomid bat abundance variation from human habitat disturbance - Carballo Morales, Jorge D. (2021)
The loss of tropical forest cover caused by land-use change is causing changes in populations of animal trophic guilds, including those belonging to Phyllostomidae bat species. They fulfill important ecosystem functions such as pollination, seed dispersion, and regulations of vertebrate and invertebrate populations in Neotropical forests and human disturbed habitats. However, the effect of habitat disturbance on the abundance of phyllostomid bats is still controversial, and it is unknown if this effect presents a phylogenetic signal, or if this abundance is influenced by the type of forest where the disturbance occurs or by the distance between disturbed habitat and conserved forest. In order to answer these new questions, an exhaustive literature review was performed followed by a series of meta-analyzes. We found 26 studies from which 829 cases (i.e. species observations; k) were extracted. Each case reported the number of individuals captured in the disturbed habitat and in the conserved forest. As effect size, the bat proportion in disturbed habitats was used. We did not use phylogenetic correction in the meta-analysis because we did not find a phylogenetic signal in the bat proportion in disturbed habitats. We found that omnivorous, carnivorous, insectivorous and hematophagous bats were sensitive to habitat disturbance, while phytophagous were tolerant. In addition, the type of habitat disturbance and the type of forest where it occurs explain the differences of bat abundance within each trophic guild. Finally, there was no effect of the type of crop, the age of the secondary forest, and the distance to a conserved forest on trophic guild bat abundance in disturbed habitats. These results could focus the conservation efforts of phyllostomid bats and the ecosystem services they provide in both anthropogenic and conserved habitats